2023
DOI: 10.1177/14574969221148078
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the coding for appendicitis, appendectomy, and diagnostic laparoscopy in the Danish National Patient Registry

Abstract: Background and objective: We aimed to validate the diagnostic accuracy of appendicitis, its severity, its description, and the surgical approach, including open or laparoscopic appendectomy and diagnostic laparoscopy, in the Danish National Patient Registry (DNPR) against information from the electronic medical records. Methods: A random sample of 1046 patients of all ages and sexes recorded in the DNPR from the Capital Region of Denmark during 2010–2015 was investigated. Patients’ admission had to include a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The positive predictive value for unspecified appendicitis increased to 99% when combined with a surgical code according to the Nordic Medico-Statistical Committee. 10 This suggests that alternative strategies for abstracting data for research may be helpful in identifying patient groups of interest. That ICD coding from the medical record may also miss events or illnesses which, though important, were not explicitly included in the physician documentation is demonstrated in a review of the accuracy of ICD-10-CM to identify self-harm events in a series looking at data from patients reporting suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive predictive value for unspecified appendicitis increased to 99% when combined with a surgical code according to the Nordic Medico-Statistical Committee. 10 This suggests that alternative strategies for abstracting data for research may be helpful in identifying patient groups of interest. That ICD coding from the medical record may also miss events or illnesses which, though important, were not explicitly included in the physician documentation is demonstrated in a review of the accuracy of ICD-10-CM to identify self-harm events in a series looking at data from patients reporting suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of the diagnostic accuracy of ICD-10-CM for appendicitis compared to chart adjudication, there was a positive predictive value of 95.3% for acute appendicitis and 67.8% for unspecified appendicitis. The positive predictive value for unspecified appendicitis increased to 99% when combined with a surgical code according to the Nordic Medico-Statistical Committee [ 10 ]. This suggests that alternative strategies for abstracting data for research may be helpful in identifying patient groups of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in contrast to most previous studies on glucocorticoid treatment and adverse postoperative outcomes, we have used a clear and precise method to define groups of glucocorticoid treatment. The appendectomy procedure codes in the Danish National Patient Registry have been shown to be highly accurate [ 40 , 41 ]; thus, the risk of misclassification for the procedure is low; however, the Danish National Patient Registry does not hold information on which laparoscopic procedures were converted to open procedures intraoperatively. Also, although Danish National Patient Registry includes “complicated appendicitis” with its corresponding diagnosis codes such as “appendicitis with generalized peritonitis,” there are no specific data on “perforation” as a cause to the complicated nature of these diagnoses in our dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of appendicitis was extrapolated from ICD-10-CM codes, which were evaluated from the day of surgery through the third postoperative day. Recent studies have demonstrated the difficulty of differentiating uncomplicated from complicated appendicitis, particularly when relying solely on ICD-10-CM diagnostic codes [ 21 , 26 , 27 ]. The clinical delineation between complicated and uncomplicated disease is also not entirely consistent in the literature.…”
Section: Methodsmentioning
confidence: 99%